Question
upstudy study bank question image url

Solve for \( x \). \[ \begin{array}{l}5^{(6 x-1)}=5^{(4 x+3)} \\ \text { A. } x=\frac{1}{2} \\ \text { B. } x=5 \\ \text { D. } x=2 \\ \text { D. } x=\frac{1}{5}\end{array} \]

Ask by Welch Griffiths. in the United Arab Emirates
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x = 2 \)

Solution

To solve the equation: \[ 5^{6x - 1} = 5^{4x + 3} \] Since the bases are the same and positive (\(5 \neq 1\)), we can set the exponents equal to each other: \[ 6x - 1 = 4x + 3 \] Subtract \(4x\) from both sides: \[ 2x - 1 = 3 \] Add \(1\) to both sides: \[ 2x = 4 \] Divide both sides by \(2\): \[ x = 2 \] **Answer:** \( \boxed{2} \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \( 5^{(6x-1)} = 5^{(4x+3)} \), we can set the exponents equal to each other since the bases are the same: \[ 6x - 1 = 4x + 3 \] Next, we will isolate \( x \): 1. Subtract \( 4x \) from both sides: \[ 6x - 4x - 1 = 3 \] which simplifies to \[ 2x - 1 = 3 \] 2. Add 1 to both sides: \[ 2x = 4 \] 3. Finally, divide by 2: \[ x = 2 \] So, the solution is \( x = 2 \). Thus, the answer is \( \text{D. } x = 2 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy